Qual a acurácia da guia cirúrgica no planejamento de cirurgias ortognáticas? Uma revisão sistemática. - Biegelmeyer, Thaís Cargnino; Goulart, Maria Eduarda Pereira (My University, 2019)
The resolutive treatment of facial skeletal alterations presents, as an alternative, orthognathic surgeries associated with orthodontic treatment, aiming at achieving the ideal dental occlusion, aesthetics and facial harmony. The transfer of preoperative planning during surgery is performed by means of a surgical guide, which orient the correct positioning of the gnatic bones according to the previously planned occlusion. This study aims to evaluate through a systematic review (SR) the accuracy of the surgical guide in the planning of orthognathic surgeries. For this, articles from the Pubmed database were selected and the keywords used were: Orthognathic Surgery. Guide (splint). Rapid Prototyping (3D printing, CAD / CAM, accuracy). From the elaboration of a flowchart, through a PRISMA protocol, the articles were evaluated by title and abstract and, from this, were read in full, considering the previously defined inclusion and exclusion criteria. As the most important inclusion criteria, should be emphasized that patients should undergo computed tomography, present maxillofacial skeletal deformities and use studies that were performed in living patients or human cadavers. Exclusion criteria were the use of the surgical guide for other dental procedures, studies that did not mention the use of the guide; Patients diagnosed with malignant lesions or congenital malformations should not have undergone previous orthognathic surgery. In this manner, 7 articles were selected for analysis of their results that analyzed the accuracy of preoperative movements in relation to postoperative results, which reported error values below 2 mm, in which the maximum error presented by the studies was well controlled up to 1.73 mm and the average error was lower. 1 mm, which is considered to be within a clinically acceptable range. However, the real accuracy of the surgical guide's accuracy could not be estimated, since none of the studies presented performed the ideal statistical test, represented by the ROC curve, to evaluate such result. In addition, because they presented information from heterogeneous and unsatisfactory statistical data, it was not possible to establish a pattern of analysis between the studies, making difficult to perform SR meta-analysis. Regarding the risk of bias in the selected studies, did not meet all the quality criteria determined by QUADAS-2, evaluated in four domains: sample selection, index test (guide accuracy, difference between planning, guide, distortion and ROC curve), reference standard, flow and timing. The reproductive capacity of the three-dimensional maxillomandibular positioning can be considered adequate and with results similar to those offered by conventional planning. Although all techniques achieved precision results, is important to highlight that the virtual method presented lower error values than the other techniques, indicating a higher planning transfer precision. [resumo fornecido pelos autores]
O tratamento resolutivo de alterações esqueléticas faciais apresenta como alternativa a realização de cirurgias ortognáticas associadas com o tratamento ortodôntico, com o intuito de alcançar a oclusão dentária ideal, estética e harmonia facial. A transferência do planejamento pré-operatório no ato cirúrgico é realizada por meio de uma guia cirúrgica, que orienta o correto posicionamento dos ossos gnáticos de acordo com a oclusão previamente planejada. O presente estudo tem como objetivo avaliar por meio de uma revisão sistemática (RS) da literatura qual a acurácia da guia cirúrgica no planejamento de cirurgias ortognáticas. Para isso, foram selecionados artigos oriundos da base de dados Pubmed, para tal pesquisa, as palavras chaves utilizadas foram: Orthognathic Surgery. Guide (splint). Rapid Prototyping (3D printing, CAD/CAM, accuracy). A partir da elaboração de um fluxograma, por meio de um protocolo PRISMA, os artigos foram avaliados, pelo título e resumo e, a partir disso, os mesmos foram lidos na íntegra, considerando os critérios de inclusão e exclusão previamente definidos. Como critérios de inclusão mais consideráveis pode-se ressaltar que os pacientes deveriam ser submetidos a Tomografia Computadorizada, apresentarem deformidades esqueléticas maxilofaciais, além de utilizarem estudos que foram realizados em pacientes vivos ou em cadáveres humanos. Destacou-se como critérios de exclusão à utilização da guia cirúrgica para outros procedimentos odontológicos, estudos que não citaram o uso da guia; pacientes diagnosticados com lesões malignas, ou com malformações congênitas e os mesmos não deveriam ter sido submetidos à cirurgia ortognática prévia. Desta forma, foram selecionados 7 artigos para análise de seus resultados, os quais analisaram a precisão dos movimentos pré-operatórios comparando aos resultados pós-cirúrgicos, os quais relataram valores de erros inferiores a 2 mm, o que é considerado dentro de uma margem clinicamente aceitável. Entretanto, a real veracidade da acurácia da guia cirúrgica não pôde ser estimada, pelo fato de que nenhum dos estudos apresentados realizou o teste estatístico ideal, representado pela Curva ROC, para avaliar tal resultado. Já com relação ao risco de viés dos estudos selecionados não preencheram todos os critérios de qualidade determinados pelo QUADAS-2, que é avaliado em quatro domínios: seleção da amostra, teste de índice (acurácia da guia, diferença entre planejamento, distorção da guia e curva ROC), padrão de referência, fluxo e tempo. A capacidade de reprodução do posicionamento maxilo-mandibular tridimensionalmente pode ser considerada adequada e com resultados semelhantes aos oferecidos pelo planejamento convencional. Ainda que todas as técnicas alcançaram resultados precisos, é importante destacar que o método virtual apresentou valores de erro inferiores aos das demais técnicas, indicando uma maior precisão de transferência de planejamento. [resumo fornecido pelos autores]
Keywords: Odontologia; Arcada ósseo dentária - Cirurgia; Face - Cirurgia; Boca - Cirurgia; Ossos faciais - Anomalias - Cirurgia.; Ortodontia corretiva